Characterization of new silicon photomultipliers with low dark noise at low temperature. (8th March 2021) - Ozaki, K.; Kazama, S.; Yamashita, M.; Itow, Y.; Moriyama, S.
Abstract: Silicon photomultipliers (SiPMs) have low radioactivity, compact geometry, low operation voltage, and reasonable photo-detection efficiency for vacuum ultraviolet light (VUV). Therefore it has the potential to replace photomultiplier tubes (PMTs) for future dark matter experiments with liquid xenon (LXe). However, SiPMs have nearly two orders of magnitude higher dark count rate (DCR) compared to that of PMTs at the LXe temperature (∼165 K). This type of high DCR mainly originates from the carriers that are generated by the band-to-band tunneling effect. To suppress the tunneling effect, Hamamatsu Photonics K.K. have developed a new SiPM with lowered electric field strength. We have characterized its performance in a temperature range of 153 K to 298 K. We demonstrated that the newly developed SiPMs have 6–60 times lower DCR at low temperatures than that of the conventional SiPMs.